A study on determinants of underreporting of adverse drug reactions among resident doctors - Gupta, Rohini; Malhotra, Apoorva; Malhotra, Pavan (International Journal of Research in Medical Sciences, 2018)
Background: Adverse Drug Reactions (ADRs) are global problem with significant morbidity and mortality. Health care providers/professionals (HCPs) play a critical role in ADR surveillance. However, only 6% of all ADRs are reported and under-reporting acts as great impedance in exchange of drug information. Thus, spontaneous reporting of suspected adverse drug reactions requires greater commitment from healthcare professionals. The aim was to determine the reasons of underreporting of ADRs among resident doctors. Methods: This was a cross-sectional observational study with self-administered questionnaire assessing the reasons for underreporting of ADRs among resident doctors. Results: Very low level of awareness about ADR reporting was found among doctors. Eighty eight percent of doctors did not know the authority and the procedure for ADR reporting. About 32.8% were not sure with the reaction and the drug, while 46.3% doctors felt that there is no need of reporting the recognized reactions again. Other factors responsible for under reporting were lack of time in 73% and cumbersome procedure in 45% of the participants. Conclusions: A poor level of awareness of pharmacovigilance was seen among doctors. Measure to improve awareness, accessible systems for reporting and effective National Programme are required to improve reporting